2019
DOI: 10.1002/chem.201805024
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry of Nucleation: In Situ Pair Distribution Function Analysis of Secondary Building Units During UiO‐66 MOF Formation

Abstract: The concept of secondary building units (SBUs) is central to all science on metal‐organic frameworks (MOFs), and they are widely used to design new MOF materials. However, the presence of SBUs during MOF formation remains controversial, and the formation mechanism of MOFs remains unclear, due to limited information about the evolution of prenucleation cluster structures. Here in situ pair distribution function (PDF) analysis was used to probe UiO‐66 formation under solvothermal conditions. The expected SBU—a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 77 publications
3
86
0
Order By: Relevance
“…[203][204][205][206] In situ PDF studies, on the other hand, allow for identication and characterization of disordered or amorphous intermediate structures and species in solution, which are important in nanomaterials. For example, in studies of nanomaterial synthesis, in situ PDF analysis gives the possibility for studying the atomic structure of the species present before, during and aer crystallization of nanoparticles, 183,[207][208][209][210][211][212][213][214][215][216][217][218][219] which is essential for gaining a deeper understanding of material nucleation processes, where atomic scale mechanistic information generally is scarce. Knowledge of the relation between chemical synthesis and the resulting atomic structure of the material is crucial in the advancement of nanoscience.…”
Section: Size-dependent Structure In Metallic Nanoparticlesmentioning
confidence: 99%
“…[203][204][205][206] In situ PDF studies, on the other hand, allow for identication and characterization of disordered or amorphous intermediate structures and species in solution, which are important in nanomaterials. For example, in studies of nanomaterial synthesis, in situ PDF analysis gives the possibility for studying the atomic structure of the species present before, during and aer crystallization of nanoparticles, 183,[207][208][209][210][211][212][213][214][215][216][217][218][219] which is essential for gaining a deeper understanding of material nucleation processes, where atomic scale mechanistic information generally is scarce. Knowledge of the relation between chemical synthesis and the resulting atomic structure of the material is crucial in the advancement of nanoscience.…”
Section: Size-dependent Structure In Metallic Nanoparticlesmentioning
confidence: 99%
“… a) Stacked PXRD patterns of selected microwave syntheses compared with the pattern for UiO‐66 predicted from CSD deposition RUBTAK . b) Plot of BET surface area (N 2 , 77 K) versus reaction time, showing that modulation in all cases produces crystalline UiO‐66 more rapidly at short reaction time.…”
Section: Resultsmentioning
confidence: 99%
“…An in situ total X‐ray scattering study carried out by Xu et al. examined the formation of the hexanuclear Zr 6 secondary building units (SBU) during the solvothermal synthesis of the archetypal zirconium terephthalate MOF UiO‐66 (Figure a), [Zr 6 O 4 (OH) 4 (BDC) 6 ] (BDC=1,4‐benzenedicarboxylate), suggesting self‐assembly occurs by the formation of SBUs in a metal salt precursor solution, followed by assembly of multinuclear clusters upon the addition of the organic linkers, and finally coalescence of these clusters to form an ordered crystalline framework . An in situ synchrotron energy dispersive X‐ray diffraction (EDXRD) study into the formation of the isoreticular Zr‐fum analogue, [Zr 6 O 4 (OH) 4 (fumarate) 6 ], in water showed that the addition of increasing equivalents of formic acid modulator to the aqueous synthesis results in a decrease in both the nucleation rate and crystal growth rate, supporting the concept of linker/modulator competition decelerating the reaction rate (typical modulators are shown in Figure b) …”
Section: Introductionmentioning
confidence: 99%
“…The method is well established for assessing structural details of inorganic centers and defects in non-ideal MOFs 33 . It has previously been used to characterize local structuring and microporosity in amorphous and nanocrystalline MOFs 34,35 , nucleation of precursors during MOF synthesis, including the isoreticular UiO-66 36,37 , and the study of temperature-driven local distortions of Zr 6 O 8 clusters in related MOFs UiO-66 and NU-1000 38 . It has also been used to probe the sub-structuring of both ions [39][40][41] and gases [42][43][44] within microporous compounds including the binding of various species to Zr 6 O 8 clusters [45][46][47][48] .…”
mentioning
confidence: 99%